(untitled) (Research, Society and Development, 2019)
Nude mice are the usual animal model for studying orthotopically implanted human tumors, and ultrasound imaging has emerged as a viable method for measuring tumors implanted orthotopically. The aim of this study was to evaluate ultrasound findings of liver tumors implanted into mice using a 13-MHz transducer and to correlate these findings with gross pathology and histological examinations. Tumor samples from liver metastases were obtained surgically from patients, and 1-mm³ fragments were implanted into the liver parenchyma of 38 nude mice. Mice were imaged monthly by ultrasound until sacrifice. Of the 38 mice implanted with tumor fragments, 11 developed tumors. Ultrasound detected nodular lesions in the 11 macroscopically positive animals and was able to identify the features of the engrafted tumors. Ultrasound imaging is a viable and noninvasive method for evaluating the liver parenchyma of nude mice, and showed 100% sensitivity and specificity in detecting and characterizing lesions.